Daily Social Interactions and the Biological Stress Response: Are There Age Differences in Links Between Social Interactions and Alpha-Amylase?. (12th December 2017) - Birditt, Kira S; Tighe, Lauren A; Nevitt, Michael R; Zarit, Steven H
Abstract: Background and Objectives: According to the strength and vulnerability integration (SAVI) model, older people are better able to avoid negative social interactions than younger people, but when they do experience negative interactions, they are equally or more emotionally and physiologically reactive than younger people. Less is known about the links between daily negative and positive social encounters and the sympathetic adrenal medullary system (a key stress pathway) and whether there are age differences in these links. This study considers whether negative and positive social interactions are associated with diurnal alpha-amylase (a measure of the sympathetic adrenal medullary system) and whether there are differences in these links by age. Research Design and Methods: Participants were from the Daily Health, Stress, and Relationship Study, which includes a random sample of 89 individuals (aged 40–95) who completed 14 days of daily diary interviews and provided saliva samples four times a day (wake, 30 min after wake, lunch, and bedtime) for four of those days that were assayed for alpha-amylase. Results: Days in which people reported more negative interactions were associated with flatter morning declines in alpha-amylase, indicating greater stress. Links between positive interactions and diurnal alpha-amylase varied by age group. Discussion and Implications: Findings are consistent with the SAVI model indicating that older adults respond differently to social stimuli than younger people.